EFFICACY OF PREVENTATIVE PARENTING INTERVENTIONS FOR PARENTS OF PRETERM INFANTS ON LATER CHILD BEHAVIOR: A SYSTEMATIC REVIEW AND META‐ANALYSIS. Issue 6 (20th October 2014) - Herd, Michael; Whittingham, Koa; Sanders, Matthew; Colditz, Paul; Boyd, Roslyn N.
ABSTRACT The aim of this systematic review was to determine the efficacy of parenting interventions for parents of preterm infants to improve child behavior. Randomized controlled trials (RCTs) of parenting interventions for parents of preterm infants were included. Searchers were conducted of PubMed from 1951 to April 2013, the Cumulative Index to Nursing and Allied Health Literature (CINAHL) from 1982 to April 2013, Scopus from 1966 to April 2013, PsycINFO from 1840 to April 2013, the Web of Science, and the Cochrane Library. Twelve RCTs were identified that assessed child behavior. Of these studies, only data from three were able to be pooled for meta‐analysis: the Infant Health and Development Program (IHDP) at 3 years, the Mother‐Infant Transaction Program (modified; MITP‐M) at 5 years, and the Victorian Infant Brain Studies (VIBeS Plus) at 4 years. Outcome from this analysis revealed a small, but significant, effect on child behavior favoring the intervention (95% CI: 0.08–0.32; p = .001). There is evidence that preterm parenting interventions can improve child behavior. Streamlined interventions such as MITP‐M and VIBeS Plus that have a strong focus on the mother–infant relationship may have greatest potential.